Impact of Quarterly Results on Share Prices - Babu, C.; Kasilingam, R. (Indian Journal of Finance, 2013)
The purpose of the present study is to find out the effect of quarterly results on share prices of securities. The Independent sample T-test was employed to compare the prices of stocks before and after the announcement of the quarterly results by the companies. The correlation between share price and Sensex was also analyzed to find out whether change in price is due to change in the market index. The change in prices was also compared to an increase in profits reported in the quarterly results. The study results show that there was an increase in price after the result, and that an increase in price is mainly due to market conditions rather than the announcement of quarterly results. The increase or decrease in share prices was not reflected in the growth in profits announced in the quarterly results.